Recycling of mine tailings for the geopolymers production: A systematic review. (June 2022) - Qaidi, Shaker M.A.; Tayeh, Bassam A.; Zeyad, Abdullah M.; de Azevedo, Afonso R.G.; Ahmed, Hemn Unis; Emad, Wael
Abstract: The mining sector generates a considerable amount of waste stone and tailings, which constitute a ‎‎substantial hazard to the ecology. The most prevalent method of disposing of these industrial ‎‎wastes is by dumping, which adds to soil deterioration and water contamination and also takes up ‎‎valuable land. Fortunately, it can be recycled in a variety of ways, including the promising ‎‎geopolymerisation technique, which converts waste into value. This article discusses recent ‎‎advances in the production of mine tailings-based geopolymers composites (MT-GPC) from waste and ‎‎industrial by-products as a potentially sustainable construction material. Besides, focusing on the ‎‎following ‎‎aspects: economic and production perspective; environmental consequences and waste ‎‎disposal; physical and chemical properties; mechanical properties; durability properties; ‎‎microstructure properties‎; thermal properties; and potential applications of MT-GPC.‎